2014
DOI: 10.1044/2014_jslhr-s-12-0412
|View full text |Cite
|
Sign up to set email alerts
|

Voice Onset Time in Consonant Cluster Errors: Can Phonetic Accommodation Differentiate Cognitive From Motor Errors?

Abstract: The data overall do not allow using (a lack of) accommodation as a diagnostic as to the processing level at which an error has occurred. The data support speech production models that allow for an integrated view of phonological and phonetic processing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
9
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 43 publications
1
9
0
1
Order By: Relevance
“…This parallel processing results in the irregularities captured by acoustic analyses. Similar patterns have been also observed in normal speakers using the tongue-twisters paradigm (Goldrick & Blumstein, 2006;Pouplier, Marin & Waltl, 2014).…”
Section: Introductionsupporting
confidence: 66%
“…This parallel processing results in the irregularities captured by acoustic analyses. Similar patterns have been also observed in normal speakers using the tongue-twisters paradigm (Goldrick & Blumstein, 2006;Pouplier, Marin & Waltl, 2014).…”
Section: Introductionsupporting
confidence: 66%
“…Momentary (within a few milliseconds) increases in amplitude of the inappropriate between-words abrupt pauses are consistent with deficits associated with state feedback control theory (Houde & Nagarajan, 2011), with possible control parameters including movement commands for respiratory, laryngeal, and articulatory targets. Phonatory behaviors as biomarkers of apraxia of speech, in particular, have attractive measurement features as they do in research in voice, dysfluency, and other motor speech disorders (e.g., Civier, Bullock, Max, & Guenther, 2013;Cohen, Renshaw, Mitchell, & Kim, 2016;Kim, 2015;Konopka & Roberts, 2016;Kumar, Croxson, & Simonyan, 2016;Ludlow, 2015;Neef, Anwander, & Friederici, 2015;Pouplier, Marin, & Waltl, 2014;Simonyan, 2013;Simonyan & Horwitz, 2011;Vanhoutte et al, 2014). In the present context, the same control mechanism underlying an abrupt inappropriate speech onset could underlie the excessive/equal sentential stress sign of CAS described previously.…”
Section: Abrupt Inappropriate Word Onsets/offsetsmentioning
confidence: 63%
“…As mentioned in the Introduction, there is clear and consistent evidence that some spoken production errors reflect properties of the target and the error, which suggests that the activation of the target influences the error response through cascading activation (unimpaired participants: Goldrick & Blumstein, 2006;McMillan & Corley, 2010;Goldrick, Baker, Murphy, & Baese-Berk, 2011;Pouplier, Marin, & Waltl, 2014;impaired participants: Kurowski & Blumstein, 2016;Laganaro, 2012). For example, Goldrick and Blumstein (2006) observed that voicing errors (e.g., /k/ → [g]) were produced with longer VOTs than accurately produced voiced consonants (e.g., /g/ → [g]), revealing the partial activation from the target /k/ in the case of the errors, and a similar finding was reported in the errors of individuals with aphasia (Kurowski & Blumstein, 2016).…”
Section: Interactivity In Spoken Productionmentioning
confidence: 99%